Single-cell DNA methylome sequencing of human preimplantation embryos. (January 2018) - Zhu, Ping; Guo, Hongshan; Ren, Yixin; Hou, Yu; Dong, Ji; Li, Rong; Lian, Ying; Fan, Xiaoying; Hu, Boqiang; Gao, Yun; Wang, Xiaoye; Wei, Yuan; et al.
Abstract DNA methylation is a crucial layer of epigenetic regulation during mammalian embryonic development1–3 . Although the DNA methylome of early human embryos has been analyzed4–6, some of the key features have not been addressed thus far. Here we performed single-cell DNA methylome sequencing for human preimplantation embryos and found that tens of thousands of genomic loci exhibited de novo DNA methylation. This finding indicates that genome-wide DNA methylation reprogramming during preimplantation development is a dynamic balance between strong global demethylation and drastic focused remethylation. Furthermore, demethylation of the paternal genome is much faster and thorough than that of the maternal genome. From the two-cell to the postimplantation stage, methylation of the paternal genome is consistently lower than that of the maternal genome. We also show that the genetic lineage of early blastomeres can be traced by DNA methylation analysis. Our work paves the way for deciphering the secrets of DNA methylation reprogramming in early human embryos. An analysis of single-cell DNA methylome sequencing data from human preimplantation embryos finds evidence for de novo methylation. Methylation reprogramming at this stage is a balance between global demethylation, which is faster in the paternal genome, and focused remethylation.